Computational model of alpha 7 nicotinic acetylcholine receptor in thalamic reticular nucleus neurons and their involvement in network states - Aman Ullah; Karen Therrien; John R. Cressman; Nadine Kabbani (PLoS ONE, 2025)
Human 15q13.3 microdeletion syndrome (15q13mds) is a genetic disorder caused by a heterozygous deletion of multiple genes, including the CHRNA7 gene, which encodes the α7 nicotinic acetylcholine receptor (α7 nAChR). This condition is associated with significant neurodevelopmental impairments and an increased risk of seizures, with studies indicating reduced α7 nAChR expression in affected individuals. To explore the role of α7 nAChR activity, we developed computational models of the thalamic reticular nucleus (TRN), a brain region critical for regulating thalamocortical (TC) oscillations involved in epilepsy and sleep-wake states. Using a single-compartment kinetic model of a TRN neuron embedded in a simplified thalamic network model, we demonstrate that α7 nAChR activity is necessary to modulate neuronal firing, through calcium regulation, and produce distinct wake and sleep-like states with the network. These findings suggest that α7 nAChR activity in the TRN modulates TC oscillations between sleep and wake states and can contribute to absence seizures in 15q13mds and other neurodevelopmental disorders.